Association of Elite Sports Status with Gene Variants of Peroxisome Proliferator Activated Receptors and Their Transcriptional Coactivator - Petr, Miroslav; Maciejewska-Skrendo, Agnieszka; Zajac, Adam; Chycki, Jakub; Stastny, Petr (International journal of molecular sciences, 2019)
BACKGROUND: Although the scientific literature regarding sports genomics has grown during the last decade, some genes, such as peroxisome proliferator activated receptors (PPARs), have not been fully described in terms of their role in achieving extraordinary sports performance. Therefore, the purpose of this systematic review was to determine which elite sports performance constraints are positively influenced by PPARs and their coactivators. METHODS: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used, with a combination of PPAR and sports keywords. RESULTS: In total, 27 studies that referred to PPARs in elite athletes were included, where the Ala allele in PPARG rs1801282 was associated with strength and power elite athlete status in comparison to subelite athlete status. The C allele in PPARA rs4253778 was associated with soccer, and the G allele PPARA rs4253778 was associated with endurance elite athlete status. Other elite status endurance alleles were the Gly allele in PPARGC1A rs8192678 and the C allele PPARD rs2016520. CONCLUSIONS: PPARs can be used for estimating the potential to achieve elite status in human physical performance in strength and power, team, and aerobic sports disciplines. Carrying specific PPAR alleles can provide a partial benefit to achieving elite sports status, but does not preclude achieving elite status if they are absent.
Keywords: Physical Endurance; alely; Athletes; PPAR alfa; Humans; sportovci; Gene Frequency; Athletic Performance; PPAR gamma; genetická variace; sportovní výkon; PPARGC1A; PPAR alpha; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; frekvence genu; Genetic Variation; lidé; fyzická vytrvalost; PPAR gama; Alleles